Paracoccidioidomycosis: epidemiological, clinical, diagnostic and treatment up-dating - Silvio Alencar Marques (Sociedade Brasileira de Dermatologia, 2013)
Paracoccidioidomycosis is an acute - to chronic systemic mycosis caused by fungi of the genus Paracoccidioides. Due to its frequent tegument clinical expression, paracoccidioidomycosis is an important disease for dermatologists, who must be up-to-date about it. This article focuses on recent epidemiological data and discusses the new insights coming from molecular studies, as well as those related to clinical, diagnostic and therapeutic aspects. In the latter section, we give particular attention to the guideline on paracoccidioidomycosis organized by specialists in this subject.